RESEARCH OF AGRO-ECONOMIC GROWTH AS A FUNDAMENTAL CATEGORY OF DEVELOPMENT OF A REGION - Zhangorazova; Bakkuev; Bagova; Kokova; Kunizheva (Revista Inclusiones, 2020)
In the context of transformational changes associated with the acceleration of global scientific and technological rhythms in all areas of the economy, the relevance of research on economic growth and development is growing. The research is aimed at identifying the main factors of growth and development of the agro-economic system at the regional level, defining mechanisms and tools for achieving the strategic goals of economic development in the context of global and local scientific and technological transformations.